2014
DOI: 10.2174/1573398x10666140429005007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Monitoring of Adherence to Inhaled Medication in Asthma

Abstract: Abstract:The main treatment of asthma is inhaled corticosteroids. However adherence to these medications in asthma is often poor, with low adherence associated with excessive health care costs and an increased risk of emergency room visits and mortality. Although various methods are used to indirectly assess adherence, all have significant limitations whether used in clinical or research practice. The recent development of electronic monitoring devices (EMDs) for use with inhalers presents an exciting opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…For example, D’Arcy et al 30 developed a Bluetooth inhaler device that used acoustic recordings of inhaler usage to monitor temporal and technique adherence and assess the correlation between clinical outcomes and adherence. Furthermore, studies using the US Food and Drug Administration (FDA)-approved Propellor Health (Madison, WI, USA) digital platform and inhalers demonstrated the feasibility of tracking inhaler usage and triggers 3134 . Moreover, individuals randomized to the Propeller Health arm had more significant reductions in inhaler usage than those under routine care 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, D’Arcy et al 30 developed a Bluetooth inhaler device that used acoustic recordings of inhaler usage to monitor temporal and technique adherence and assess the correlation between clinical outcomes and adherence. Furthermore, studies using the US Food and Drug Administration (FDA)-approved Propellor Health (Madison, WI, USA) digital platform and inhalers demonstrated the feasibility of tracking inhaler usage and triggers 3134 . Moreover, individuals randomized to the Propeller Health arm had more significant reductions in inhaler usage than those under routine care 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Early methodologies encompass electronic or mechanical meters integrated into the device, activated with the drug delivery button. Howard et al [16] reported the existence of several such devices, able to record the time of each drug actuation, or the total number of them. The use of audio analysis came up later as a method, which can characterize the quality of inhaler usage, while, also, monitoring the timings of each audio event.…”
Section: Related Workmentioning
confidence: 99%
“…10 12 13 The stakeholders who should have access to the data produced by EMDs have not been determined. However, if data indicating a patient's inhaler use was putting their health at risk were available to a healthcare professional, but was not acted on, they could be open to criticism for not intervening.…”
Section: Key Messagesmentioning
confidence: 99%
“…However, if data indicating a patient's inhaler use was putting their health at risk were available to a healthcare professional, but was not acted on, they could be open to criticism for not intervening. 10 This potentially major issue is highlighted by a recent clinical trial using EMDs where researchers reported 'extreme overuse' of β-agonists in 26% of their 152 participants, with these patients actuating 32 or more doses of reliever inhaler a day. 14 To understand the potential benefits and issues that EMDs could create for the asthma care system, it is important to involve asthma stakeholders in the introduction of these devices, to help ensure they are ultimately safe and effective.…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation